Acoustic emission method for facilitating decision making about the safety of structures being elements of smart cities. (January 2019) - Świt, G; Adamczak, A; Krampikowska, A
Abstract: Smart City concept is called the concept of the future and it relates to the so-called intelligent cities. Currently, it is the most promising idea aiming at their development, as well as to the development of local economy. Smart City is a response to the changes that have been occurring in the whole world, relating to both expansion and functioning of the cities that become more intelligent every year. Modern agglomerations should use the newest information and communication technologies in such a manner that they increase the interactivity and the effectiveness of urban infrastructure, but also in order to raise the awareness of the residents. Every city that wants to become smart should include numerous aspects connected with urban life in its development plan. One of the factors ensuring the effectiveness of city functioning is Smart Building, which is an intelligent, environmentally friendly construction, and most of all, it is safe for people. Ensuring the safety of the construction requires performing a series of diagnostic operations in all phases of construction object's life cycle. As the result of the influence of external factors on the structure, including environmental factors, and as the result of useful loads that change during long-time exploitation, the objects are subject to degradation. Early and precise detection of damages that occurred during the use allows to take reasonable measures, including repairs, ensuring uninterrupted exploitation of the object. Therefore, especially in the recent period, a lot of attention has been paid to the topic of diagnostics and monitoring of the structures being exploited, and it is connected with the issue of durability and assurance of reliability of these structures. The article presents the application of acoustic emission methods for monitoring the condition of the construction. Complete usefulness of the AE method applied in monitoring the destructive processes in structures was confirmed, especially that it allows to assess the occurring destructive processes in the conditions of real exploitative loads. It was shown that the presented method is a successful diagnostic tool enabling effective and safe functioning of intelligent city.